KERAGAMAN DAN DISTRIBUSI GASTROPODA PADA EKOSISTEM MANGROVE DESA PENAGAN PULAU BANGKA - Febriyanti, Ade; Irwanto, Riko; Supratman, Okto (BRIN Publishing (Penerbit BRIN), 2025)
Penagan Village's mangrove area has high ecological and economic value. Aquatic biota such as gastropod groups inhabit the mangrove ecosystem here. The community makes extensive use of these animals for consumption and trade. The purpose of this research is to identify species, analyze the diversity, density, and distribution patterns of gastropods in the Penagan Village mangrove area. In addition, the species and density of mangroves will be identified, as will the relationship between gastropods and environmental factors in the area. This study was carried out between September 2020 and January 2021. Purposive sampling of mangrove vegetation was used to collect data at three different stations. The gastropods found were 1989 individuals from eight families: Cerithiidae, Ellobiidae, Littorinidae, Muricidae, Nassariidae, Neritidae, Potamididae, and Thiaridae. The highest diversity index value, 2.13, was discovered at station II, while the lowest value, 1.08, was discovered at station I. Station 3 had the highest species density and relative density of gastropods, which was 7.70 (individual/m2). Gastropods are distributed uniformly at each observation station. Rhizophora apiculata, Avicennia alba, Ceriops decandra, and Lumnitzera racemosa are the four mangrove species. The last species has the greatest density of mangroves.